Physical demands and physiological response of soccer referees in high-level matches: A systematic review - Zhang, L.; Geok, S. K.; Wazir, M. R. W. N.; Qin, L. (PLOS ONE, 2025)
Background The match physical demands placed on soccer referees are intrinsically connected to their capacity to make accurate judgments, becoming the second most studied theme in associate soccer refereeing.